From neural signatures of emotional modulation to social cognition: Individual differences in healthy volunteers and psychiatric participants - Ibañez, Agustin Mariano (2013)
It is commonly assumed that early emotional signals provide relevant information for social cognition tasks. The goal of this study was to test the association between (a) cortical markers of face emotional processing and (b) social-cognitive measures, and also to build a model which can predict this association (a and b) in healthy volunteers as well as in different groups of psychiatric patients. Thus, we investigated the early cortical processing of emotional stimuli (N170, using a face and word valence task) and their relationship with the social-cognitive profiles (SCPs, indexed by measures of theory of mind, fluid intelligence, speed processing and executive functions). Group comparisons and individual differences were assessed among schizophrenia (SCZ) patients and their relatives, individuals with attention deficit hyperactivity disorder (ADHD), individuals with euthymic bipolar disorder (BD) and healthy participants (educational level, handedness, age and gender matched). Our results provide evidence of emotional N170 impairments in the affected groups (SCZ and relatives, ADHD and BD) as well as subtle group differences. Importantly, cortical processing of emotional stimuli predicted the SCP, as evidenced by a structural equation model analysis. This is the first study to report an association model of brain markers of emotional processing and SCP.